Perancangan Video Promosi Desa Beji untuk Meningkatkan Brand Awareness - Jozua F Palandi; Ahmad Ufi Amrullah; Rahmat Kurniawan; Adita Ayu Kusumasari (MAVIS : Jurnal Desain Komunikasi Visual, 2022)
Beji Village is one of several villages in the Junrejo District area which is located on the main road to Batu City. Beji Village is divided into three hamlets: Krajan Sae, Sawahan, and Karang Jambe. Most of the residents of Beji Village work at home as tempe producers. However, the community is still not familiar with tempe made by Beji Village, including its processed products. This is due to the lack of promotion from the villagers themselves. Designing this promotional video requires several methods. Starting from the data collection stage which was carried out by interviews, observation, documentation, and questionnaires. Next, we conducted a literature study and conducted an analysis using the SWOT analysis technique. The promotional media used is video media. This promotion entitled "Tempenesia" which uses the concept of story telling and inserts the concept of soft selling of processed products in it. The final test results from this Video got a total score of 566 out of a maximum total score of 572 in the very good category.